2007
DOI: 10.4049/jimmunol.178.6.3944
|View full text |Cite
|
Sign up to set email alerts
|

Fever-Like Hyperthermia Controls T Lymphocyte Persistence by Inducing Degradation of Cellular FLIPshort

Abstract: Fever has a major impact on immune responses by modulating survival, proliferation, and endurance of lymphocytes. Lymphocyte persistence in turn is determined by the equilibrium between death and survival-promoting factors that regulate death receptor signaling in these cells. A potential integrator of death receptor signaling is the caspase-8 inhibitor c-FLIP, the expression of which is dynamically regulated, either rapidly induced or down-regulated. In this study, we show in activated primary human T lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 86 publications
1
27
0
Order By: Relevance
“…19,24,25 Our previous studies have shown that ubiquitylation-mediated isoform-specific regulation of c-FLIP stability is vital for death receptor responses upon erythroid differentiation and lymphocyte persistence during hyperthermia. 26,27 In this study, we uncovered how c-FLIP is regulated by phosphorylation, as we identified S193 as a novel in vivo phosphorylation site of all c-FLIP proteins and demonstrated that S193 phosphorylation opposes c-FLIP ubiquitylation. Furthermore, although S193A mutation rendered all c-FLIP proteins susceptible for ubiquitylation, S193 phosphorylation selectively increased the stability of c-FLIP S and c-FLIP R .…”
Section: Phosphorylation Of C-flip By Pkcmentioning
confidence: 99%
“…19,24,25 Our previous studies have shown that ubiquitylation-mediated isoform-specific regulation of c-FLIP stability is vital for death receptor responses upon erythroid differentiation and lymphocyte persistence during hyperthermia. 26,27 In this study, we uncovered how c-FLIP is regulated by phosphorylation, as we identified S193 as a novel in vivo phosphorylation site of all c-FLIP proteins and demonstrated that S193 phosphorylation opposes c-FLIP ubiquitylation. Furthermore, although S193A mutation rendered all c-FLIP proteins susceptible for ubiquitylation, S193 phosphorylation selectively increased the stability of c-FLIP S and c-FLIP R .…”
Section: Phosphorylation Of C-flip By Pkcmentioning
confidence: 99%
“…It has also been found that heat shock sensitizes cells to CD95-mediated apoptosis in Jurkat and HeLa cells, independently of the expression of Hsp70 (9,10). The study demonstrated that a 30-min heat shock treatment is sufficient to decrease the levels of c-FLIP L and c-FLIP S and to sensitize the cells to apoptosis mediated by death receptors.…”
mentioning
confidence: 68%
“…To fit experimental data, the model incorporates both the long and short c-FLIP isoforms to account for their different reaction mechanisms. The two short c-FLIP isoforms, c-FLIP S and c-FLIP R , have been shown to affect caspase-8 activation and apoptosis sensitivity in a similar way (8,10,27,33), and they have similar half-lives. As the c-FLIP property that is important for this study is its half-life, and as the half-lives of the short forms of c-FLIP, i.e.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations